2023
DOI: 10.1155/2023/7274309
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity and Synergistic Effects of Thymol-Loaded Poly (Lactic-Co-Glycolic Acid) Nanoparticles with Amikacin against Four Salmonella enterica Serovars

Abstract: Background. Salmonella species are frequently linked to biofilm-associated infections. Biofilm formation intensively reduces the efficacy of antibiotics and the host immune system. Therefore, new therapeutic strategies are needed. Thymol, the main monoterpene phenol found in Thymus vulgaris, has been shown to possess potent antibiofilm activity. Our previous findings showed that thymol enhanced the antibiofilm activity of aminoglycosides against Salmonella enterica serovars. However, the clinical potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…A similar trend was reported by several authors [49,50] after the determination of MIC and MBC correlations following the incubation of selected bacteria with extracts and/or essential oil from plants. Other authors reached similar conclusions while working on the influence of natural and synthetic compounds vis-à-vis the kinetics of bacterial mortality as a function of time (time-kill kinetics) [51][52][53][54][55]. The observed antibacterial activity might be attributed to the presence of a number of monoterpenes (E-anethole, methyl isoeugenol, myrcene sabinene and γ-terpinene) in the plant, which were mainly dominated by E-anethole (70.77%).…”
Section: Discussionsupporting
confidence: 53%
“…A similar trend was reported by several authors [49,50] after the determination of MIC and MBC correlations following the incubation of selected bacteria with extracts and/or essential oil from plants. Other authors reached similar conclusions while working on the influence of natural and synthetic compounds vis-à-vis the kinetics of bacterial mortality as a function of time (time-kill kinetics) [51][52][53][54][55]. The observed antibacterial activity might be attributed to the presence of a number of monoterpenes (E-anethole, methyl isoeugenol, myrcene sabinene and γ-terpinene) in the plant, which were mainly dominated by E-anethole (70.77%).…”
Section: Discussionsupporting
confidence: 53%
“…Antibiotic-loaded polymer nanoparticles have been detected for their high physical characteristics and antibiofilm efficacy, so they could be used as drug delivery vehicles in the treatment of bacterial biofilm with low doses. Tokam et al ( 2023) found that thymol-loaded PLGA nanoparticles showed that MBEC and MBIC of Salmonella typhi, S. typhimurium, and S. choleraesuis were reduced by 32 to 128-fold [57], which was more effective than (8 to 32 times) free thymol. This is because of the high interaction between them and biofilms.…”
Section: Biofilm Inhibition and Eradication Assays On Microtiter Platesmentioning
confidence: 99%
“…The synergy of EOs and different antibiotics/drugs in nanoformulations has also been evaluated in different biofilms. In this context, the combination of thymol-loaded NPs and amikacin antibiotics was evaluated in Salmonella enterica serovars , which causes typhoidal and nontyphoidal salmonellosis [ 148 ]. The authors reported that the minimum biofilm inhibitory concentration was reduced four to eight times with the synergistic mechanism compared with the inhibition of amikacin alone.…”
Section: Antibiofilm Efficacy Of Eos-loaded Chitosan and Other Biopol...mentioning
confidence: 99%